Rāmāẏaṇa - Candrāvatī,Ghoṣa, Naẏāncāṃda (Paścimabaṅga Bāṃlā Ākādemi, 2023)
Epic poem on Rāma (Hindu deity) and Candrābatī, active 17th century, women poet.
Epic poems
Keywords: Rāma; Candrābatī; Rāma; (Hindu deity); Poetry.; Candrābatī; active 17th century; Poetry.; Epic poetry; Bengali.; Epic poetry; Bengali